The effect of CrossFit training in developing the special strength of table tennis players - Hamaadi, Hamdullah Abed (International Journal of Psychosocial Rehabilitation, 2020)
The sport of table tennis has a training characteristic like other sports as it depends on the development of the special physical variables represented by explosive ability and characteristic of speed, and work to develop these variables in order to improve the achievement within this event. It is the focus on developing some physical abilities represented by explosive ability characterized by speed, and for this reason the researcher decided to enter into this problem through preparing CrossFit exercises that work to develop the special strength of young boxers, and the goal of the research is to prepare Cross Fit exercises, and to identify the extent of the effect of prepared exercises In the CrossFit method to develop the special strength of young boxers, as for the research hypotheses, there are statistically significant differences between the pre and post- tests of special strength among the members of the research sample for the experimental group and in favor of the post test, there are statistically significant differences between the pre and post- tests of the special strength of the members of the research sample of the control group and in favor of Post-test, there are statistically significant differences b The dimensional tests of the special strength of the two research groups are in favor of the experimental group. The researcher used the experimental approach designed by the control and experimental groups, and the research sample included the players of Anbar Club and Kateen Table tennis Club, which numbered (16) boxers, who were divided equally into two control and experimental groups, and then the researcher conducted exploratory experiments on the research sample to find out the negatives that may accompany the main experiment Then, field procedures for research were started, including pre-tests, implementing assistive exercises and conducting post-tests, and after extracting the results, they were statistically processed for the purpose of analyzing and discussing them.